Ageing population: revamp, enhance residential care homes - Chee, Kwan Foong*; Long, Chiau Ming *; Leow, Serena Wai Yee * (New Straits Times Press (M) Bhd., 2023)
As the ringgit goes through a phase of depreciation, we find ourselves not only confronted with a challenge but also an unexpected opportunity to usher in a positive shift in our society.